(untitled) (Research, Society and Development, 2021)
Objective: objective to demonstrate the importance of using Google Maps as a didactic resource applied in the territorialization of health in a virtual way. Methodology: This is an experience report, which describes reflections and aspects experienced in relation to the application of Google Maps in the territorialization in primary care. Results: The possibility offered by Google maps to perform territorialization in health in a virtual way, provided the student with the opportunity to know the territory even in times of social isolation and proved to be a very effective geotechnological tool in the process of territorialization, thus contemplating all the objectives proposed in the roadmap for virtual territorialization. The mapping and georeferencing, using Google maps, aim to make the process of territorialization somewhat continuous, favoring the approximation between professionals and the population. Conclusion: Google maps has great potential as a didactic resource, as it proved to be effective in promoting an approximation with the spatial and social reality, contributing to a better understanding of students in the aspects addressed during the process of territorialization in health carried out in primary care.